Weather and climate through infographics - Rowell, Rebecca; Dean, Venitia (Minneapolis Lerner Publications company, 2014)
This book covers weather and climatology, including weather-related disasters, how weather impacts us as humans, what patterns occur with weather and within different climates, and how we measure and predict those things"--Provided by publisher
Includes index
3
Keywords: Climatology .?(3ZjQ ebffs; Weather.?(3ZjQ ebffs